Effect of Replacing Wheat Bran with Acacia seyal Pods on the Performance of Tigray Highland Sheep - Weldegebriel, Berhe; Yadav, K. R. (Indian Journal of Animal Nutrition, 2017)
Twenty Tigray Highland sheep were divided into 5 groups of 5 animals each using randamised block design. The animals were fed ad lib. grass hay (basal ration), basal ration + 306 g of Acacia seyal pods (100%), basal ration + 204 g (66.7%) Acacia seyal pods and 102 g (33.3%) wheat bran, basal ration + 102 g (33.3%) of Acacia pods and 204 g (66.7%) wheat bran, basal ration + 306 g (100%) wheat bran in groups T1, T2, T3, T4 and T5, respectively during a feeding trial of 90 days. Carcass evaluation was done at the end of the digestibility trial. Total DM, OM and CP intakes were higher (P